DETERMINE THE FACTORS THAT INFLUENCE PATIENTS’ COMPLIANCE IN THE TREATMENT OF OVARIAN CANCER CHEMOTHERAPY AT THE Dr. PIRNGADI HOSPITAL MEDAN IN 2019 - meri siska sirait (Fakultas Kesehatan Masyarakat, Institut Kesehatan Deli Husada Deli Tua, 2020)
Ovarian cancer is the most gynecological malignancy that causes death and it is one of the high incidences with around 192,000 cases worldwide in 2018. Non compliance to treatment of patients with ovarian cancer can cause of trigger stress, consequently, it does affect the physical condition and the psychological. The purpose of this research was to determine the factors that influence patients’ compliance in the treatment of ovarian cancer chemotherapy at the Dr. Pirngadi Hospital Medan in 2019. The method used for this research was observational analytic design with a cross- sectional approach. This research was conducted at the Dr. Pirngadi Hospital Medan in February - May 2020. The population in this research was 97 ovarian cancer patients who have chemotherapy and the samples were 45 patients collected by consecutive sampling technique. The results of the research showed that there is no influence of age factors on chemotherapy compliance as p (0.437) > α (0.05);there is no influence of educational factors on chemotherapy compliance as p (0.435) > α (0.05); there is an effect of occupational factors on chemotherapy compliance as p (0.036)